1991
DOI: 10.1002/mus.880140703
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine in muscle, serum, and urine of nonprofessional athletes: Effects of physical exercise, training, and L‐carnitine administration

Abstract: Efficient utilization of fatty acids to sustain prolonged physical efforts is thought to be dependent on the carnitine shuttle of muscle. A study has been carried out in 24 athletes (13 long-distance runners and 11 sprinters). These subjects received placebo or L-carnitine (1 g/orally b.i.d.) during a 6-month period of training. In endurance athletes, training induced lowering of total and free muscle carnitine. Increase of esterified muscle carnitine was also observed. Post-exertional overflow of acetylcarnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 15 publications
3
33
0
2
Order By: Relevance
“…During placebo, there was no change in the total carnitine response to exercise; however, free carnitine was significantly reduced at 30 and 120 min postexercise, and there was a slight increase in acetylcarnitine. A decrease in serum free carnitine and an increase in acetylcarnitine after intense exercise is in agreement with other studies that have examined carnitine responses to exercise (1,9). Although there are proportional changes in free and acetylcarnitine in muscle during exercise, it is generally accepted that the total muscle carnitine concentration is not altered during exercise and does not interact significantly with carnitine metabolism in the circulation (10).…”
Section: Discussionsupporting
confidence: 90%
“…During placebo, there was no change in the total carnitine response to exercise; however, free carnitine was significantly reduced at 30 and 120 min postexercise, and there was a slight increase in acetylcarnitine. A decrease in serum free carnitine and an increase in acetylcarnitine after intense exercise is in agreement with other studies that have examined carnitine responses to exercise (1,9). Although there are proportional changes in free and acetylcarnitine in muscle during exercise, it is generally accepted that the total muscle carnitine concentration is not altered during exercise and does not interact significantly with carnitine metabolism in the circulation (10).…”
Section: Discussionsupporting
confidence: 90%
“…Our study also showed that NEC levels slightly decreased and that ASAC levels increased with a CON or CAF trial. This alternation of CAR levels was explained by the enhanced oxidation of both pyruvate and fatty acids in muscles during prolonged exercise (49). Plasma CAR concentrations at exhaustion time were significantly increased in CAR-supplemented groups.…”
Section: Discussionmentioning
confidence: 92%
“…This decrease has been suggested as one of the mechanisms for the reduction of plasma fatty acid and intramuscular triacylglycerol oxidation during high-intensity exercise [91]. Accordingly most studies showed improved maximum oxygen consumption, reduced lactate accumulation, and increased high-intensity exercise performance in professional and nonprofessional athletes, especially when L-carnitine was supplemented for longer periods and at higher doses [92][93][94][95]. However, some investigations failed to show any effect of carnitine supplementation following on high-intensity training programs [96][97][98][99][100][101].…”
Section: Carnitinementioning
confidence: 99%